STUDI KELAYAKAN PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA UAP 2X50 MW DENGAN MENGGUNAKAN BOILER CIRCULATING FLUIDIZED BED COMBUSTION DI KENDARI, SULSELRABAR - Redaksi Tim Jurnal (Energi & Kelistrikan, 2017)
This research is an explanation from feasibility study of the project; Which aims to analyze the feasibility of financially the development of Power Plant (PLTU) Capacity 2 × 50 MW by using boiler circulating fluidized bed combustion (CFB). Indicators used to analyze the feasibility of Power Plant (PLTU) Capacity 2 × 50 MW are: payback period, net present value (NPV), internal rate of return (IRR), sensitivity analysis, variable operating costs, and fixed operating costs. This research analyzes investment feasibility and risk from financial aspect by considering interest rate of loan (in USD) equal to 6% per year. The calculation of the value of investments made amounted to 1074.63 USD / kW, and net present value (NPV) of 61.8270 million USD with an internal rate of return (IRR equity) of 14 percent, and the results of this study has also been calculated payback period (PP) during 6.69 years, very feasible, because it is shorter than the project age (30 years); Then it can be concluded that the tariff of selling electricity after levelized is 8.1582 Cent US $